Invasiveness of the Yersinia pestis ail protein contributes to host dissemination in pneumonic and oral plague. (April 2020) - Zhang, Yingmiao; Ying, Xiaoling; He, Yingxia; Jiang, Lingyu; Zhang, Song; Bartra, Sara Schesser; Plano, Gregory V.; Klena, John D.; Skurnik, Mikael; Chen, Hongxiang; Cai, Huahua; Chen, Tie
Abstract: Yersinia pestis, a Gram-negative bacterium, is the etiologic agent of plague. A hallmark of Y. pestis infection is the organism's ability to rapidly disseminate through an animal host. Y. pestis expresses the outer membrane protein, Ail (Attachment invasion locus), which is associated with host invasion and serum resistance. However, whether Ail plays a role in host dissemination remains unclear. In this study, C57BL/6J mice were challenged with a defined Y. pestis strain, KimD27, or an isogenic ail -deleted mutant derived from KimD27 via metacarpal paw pad inoculation, nasal drops, orogastric infection, or tail vein injection to mimic bubonic, pneumonic, oral, or septicemic plague, respectively. Our results showed that ail -deleted Y. pestis KimD27 lost the ability to invade host cells, leading to failed host dissemination in the pneumonic and oral plague models but not in the bubonic or septicemic plague models, which do not require invasiveness. Therefore, this study demonstrated that whether Ail plays a role in Y. pestis pathogenesis depends on the infection route. Highlights: Yersinia pestis Ail protein promotes host dissemination in pneumonic and oral plague. The role of Yersinia pestis Ail protein in pathogenesis depends on infection routes. Ail plays roles in invasion and serum resistance in different lineages of Y. pestis .